Decoction of bay leaf (syzygium polyanthum) against the reduction of high blood pressure in 3-month injectable birth control receptors - S, Irmawati; Rosdianah, Rosdianah; Wahyuningsih, Tia Yulita; Yunus, Muh (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Hypertension or high blood pressure is a serious health problem and has the potential to trigger various complications, such as heart disease and stroke. Bay leaf (Syzygium polyanthum), which is traditionally used as an herbal medicine, is known to contain bioactive compounds such as flavonoids, tannins, and saponins, which have the potential to lower blood pressure. However, research on the effectiveness of bay leaf decoction in 3-month injectable birth control receptors is still limited. Objective: This study aims to evaluate the effect of bay leaf decoction (Syzygium polyanthum) on the reduction of high blood pressure in 3-month injectable birth control receptors. Methods: This study uses a quasi-experimental method with a pre-test and post-test design in one group. A total of 60 respondents who were long-term acceptors of 3-month injectable birth control with high blood pressure were selected purposively. The respondents were given a decoction of bay leaves every day. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. Data were analyzed using a paired t-test to determine the significant difference between blood pressure before and after the intervention. Result: The study showed a significant decrease in systolic and diastolic blood pressure after administering bay leaf decoction. The average decrease in systolic blood pressure was 12 mmHg, and diastolic blood pressure was eight mmHg after 14 days of consumption. The paired t-test showed a p< value of 0.05, indicating a significant difference between blood pressure before and after the intervention. Conclusion: Bay leaf decoction (Syzygium polyanthum) significantly lowers high blood pressure in 3-month injectable birth control receptors. These results suggest that bay leaf can be a potential complementary therapy in the management of hypertension, especially for those who use long-term hormonal contraceptives. Although the results of this study are promising, more research with larger sample sizes and extended intervention periods is needed to confirm these findings and assess the long-term safety of using bay leaf decoction